2006
DOI: 10.1021/ja0654579
|View full text |Cite
|
Sign up to set email alerts
|

All-Photonic Molecular Half-Adder

Abstract: One molecule acts as both an AND and an XOR Boolean logic gate that share the same two photonic inputs. The molecule comprises a half-adder, adding two binary digits with only light as inputs and outputs, and consists of three covalently linked photochromic moieties; a spiropyran and two quinoline-derived dihydroindolizines. The AND function is based on the absorption properties of the molecule, whereas the XOR function is based on an off-on-off response of the fluorescence to the inputs that results from inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 35 publications
1
75
0
Order By: Relevance
“…20 Recent implementations include a half-adder, 21 2:1 digital multiplexer, 22 and 1:2 demultiplexer. 23 A digital encoder converts data into a code.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent implementations include a half-adder, 21 2:1 digital multiplexer, 22 and 1:2 demultiplexer. 23 A digital encoder converts data into a code.…”
Section: Introductionmentioning
confidence: 99%
“…By using light of carefully selected wavelengths in the UV and the visible region of the spectrum, the independent isomerization of the photochromes Indeed, by the use of three photonic inputs in the UV (302 nm, 366 nm, and 397 nm) and two in the visible (green light and red light), together with output readings at five different wavelengths, we showed that the triad can perform the functions of 13 logic devices. These include the half-adder, [56][57][58] half-subtractor, multiplexer, [16] demultiplexer, [15] encoder, [18] decoder, [18] keypad lock, [21] and reversible logic gates. [23,59,60] Moreover, all functions were operated with one common initial state (FGo-DTEo), many of them in parallel and all of them resettable by the universal application of green light (see Scheme 5).…”
Section: All-photonic Switching As Idealized Approach Toward Moleculamentioning
confidence: 99%
“…Most circuits implemented in laboratory experiments so far are one-bit half-adders. Half-adders and their component gates are realised using enzymatic networks [38,33,10,30,27], photonic molecular devices [7,8,25], quantum logic inside a single molecule [18], molecular structural circuits [19,32], acellular slime mould [40,3,28,41], nuclear magnetic resonance [36], ribosomes and mRNAs [35], peptide networks [9], and excitable chemical media [23,21,16,22]. In excitable chemical media signal careers are excitation waves; the signals are modified via interaction between the excitation waves or wave-fragments.…”
Section: Introductionmentioning
confidence: 99%